Jennifer Evans, Paul Betts, and Stefan-Ludwig Hoffmann, eds. The Ethics of Seeing: Photography and Twentieth-Century German History. Berghahn Books, 2018. - Richard Bodek (Studies in 20th & 21st Century Literature, 2019)
Review of Jennifer Evans, Paul Betts, and Stefan-Ludwig Hoffmann, eds. The Ethics of Seeing: Photography and Twentieth-Century German History. Berghahn Books, 2018. xii + 293 pp.
Keywords: Book Review; Photography; Germany